KEMAMPUAN PENGGUNAAN STRUKTUR BERPIKIR DAN PIRANTI KEBAHASAAN TEKS ANEKDOT SISWA KELAS X DI KOTA MATARAM - Adha, Isna; Mahsun; Mahyudi, Johan (Universitas Negeri Surabaya, 2021)
This study aims to measure the ability of class X students in the city of Mataram in producing anecdotal texts in Indonesian language learning. The research data collection was carried out by the method of observation and documentation with the technique of free competency involvement. The analysis of the research was carried out qualitatively and quantitatively by connecting the intralingual equivalent method of link-to-equalize, connect-to-differentiate, and link-to-equalize the main things for secondary education students in the city of Mataram and to smooth the course of the research 113 students were selected as samples. provided that all students have received the same learning. The results showed that the students' ability in producing anecdotal literary genre texts ran quite well. This research was conducted to see the results of students 'writing skills at the intermediate level and is expected to be successful in helping improve students' writing skills in producing texts.